Analisis Pengembangan Media Pembelajaran Matematika Berbasis Kearifan Lokal untuk Meningkatkan Pemahaman Siswa Kelas V SD - Amirah, Naswa; Nasution, Mai Saroh; Tondang, Bella; Giawa, Serniman Julita; Ketaren, Maya Alemina (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
This study aims to analyze the development of local wisdom-based mathematics learning media to improve students' understanding, especially at the elementary level. The research method used is the literature study method by collecting and reviewing library data which is then linked to the research. The results of the study indicate that local wisdom-based learning media have a significant positive impact on mathematics learning in elementary schools, so that the learning process can integrate local culture to maintain existing traditions in Indonesia.